Crystallinity-Controlled Atomic Layer Deposition of Ti-Doped ZrO2 Thin Films - Seokhwi Song; Eungju Kim; Kyunghoo Kim; Jangho Bae; Jinho Lee; Chang Hwa Jung; Hanjin Lim; Hyeongtag Jeon (ECS Advances, 2024)
We investigated Ti-doped ZrO _2 deposition using a cyclopentadienyl tris(dimethylamino) zirconium (CpZr(NMe _2 ) _3 ) precursor and a titanium tetraisopropoxide (TTIP) precursor using an O _3 thermal atomic layer deposition process. In addition, the effect of Ti doping concentration on the chemical bonding and electrical properties of the Ti-doped ZrO _2 thin films was studied. O _3 was used at a high concentration of 400 g m ^−3 . We varied the Ti doping concentration by controlling the rate of the supercycle process in the ZrO _2 process window of 200 °C–300 °C. As a result, the highest dielectric constant was observed at a Ti doping concentration of 2.5% because it enhances the crystallinity of ZrO. Excessive Ti doping hinders crystal formation.